Risk Matters: Breaking Certainty Equivalence - Juan Carlos Parra-Alvarez; Hamza Polattimur; Olaf Posch (Center for Economic Studies and ifo Institute (CESifo), 2020)
In this paper we use the property that certainty equivalence, as implied by a first-order approximation to the solution of stochastic discrete-time models, breaks in its equivalent continuous-time version. We study the extent to which a first-order approximated solution built by perturbation methods accounts for risk. We show that risk matters economically in a real business cycle (RBC) model with habit formation and capital adjustment costs and that neglecting risk leads to substantial pricing errors. A first-order approximation in continuous time reduces pricing errors by 90 percent relative to the certainty equivalent linear solution.
Keywords: C02; C61; C63; E13; E32; G12; 330; certainty equivalence; perturbation methods; pricing errors